Effets d’Acacia senegal (L.) Willd. sur le Rendement du Niébé (Vigna unguiculata) au Niger, Afrique de l’ouest - Saidou, Addam Kiari; Hassane, Moussa; Abdoullatif, Youchaou Tawaye; Karimou, Ambouta (European Scientific Journal, ESJ, 2018)
This paper focuses on the influence of Acacia senegal on soil and cowpea production (Vigna unguiculata) at the N'Dounga Forest Station (INRAN) through a complete randomized block design. Treatments based on its association with cowpea in isolated trees and planting were applied. Chemical parameters, nitrogen fixation potential, and cowpea production were evaluated under these treatments. The results show an improvement in the chemical property of the soil in the presence of A. Senegal. Since the pH is acidic irrespective of the modality, the analysis of the variance shows a highly significant difference between the control and the other treatments for the water pH (P <0.000 1). Also, the nitrogen fixation potential cowpea was better expressed in his presence. However, the A. Senegal has less influenced the production of cowpea. The yields of pods, seeds, and fodder were reduced compared to the control. This study also revealed the dynamics of mineral elements after harvests, which reassures producers about the sustainability of the tree/crop system.